1997
DOI: 10.1007/bf01526190
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of a calcium-binding protein (spot35/calbind in-D28k) in mouse olfactory cells: Possible relationship to neuronal differentiation

Abstract: We used immunohistochemistry to investigate the expression of spot35/calbindin-D28k (calbindin) in mouse olfactory epithelium during development. Cell stages of immunopositive olfactory cells were determined by comparing the levels of proliferating cell nuclear antigen (PCNA). Calbindin-positive cells were abundant in the middle layer of the epithelium of animals before 2 weeks of age and gradually diminished during development. Only low levels were detectable near the basement membrane in the adult. Changes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In our present study, we observed postnatal changes in dividing cells by using PCNA antiserum immunohistochemical staining [5,13]. The dividing cells varied markedly in number and arrangement during development.…”
Section: Discussionmentioning
confidence: 67%
“…In our present study, we observed postnatal changes in dividing cells by using PCNA antiserum immunohistochemical staining [5,13]. The dividing cells varied markedly in number and arrangement during development.…”
Section: Discussionmentioning
confidence: 67%
“…Transcriptomic analysis of the Prokr2+ Pioneer/TN cells revealed an enriched expression of the putative Grueneberg ganglia marker Pde2a (Zhi Huang, 2018), Pcsk1n, Tmem130, and Resp18. In addition to these, in the Migratory Prokr2+ cells, we identified the expression of several previously reported antigens for the putative terminal nerve/pioneer neurons, such as Calbindin1 (Fujiwara et al, 1997) (Fig. 9), Lhx2 (Palaniappan et al, 2019) (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…In D. rerio , while S100 CBP was observed in crypt ORNs, CR widely occurred in ORNs (Castro et al., 2006; Germanà et al., 2007). Although scgn has not been reported in the ORNs of other vertebrate species, development‐stage dependent expression of CB, CR, calmodulin, and neurocalcin was observed in rodent ORNs (Bastianelli et al., 1995; Fujiwara, et al., 1997). Expression of an EF‐hand calcium sensor, visinin‐like protein (VILIP), was observed in the olfactory sensory cells of rat (Boekhoff et al., 1997).…”
Section: Discussionmentioning
confidence: 99%